2012
DOI: 10.1111/1755-6724.12020
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Chemical Composition of Ludwigite from Vranovac Ore Deposit (Boranja Mountain, Serbia)

Abstract: The crystal structure of ludwigite from Vranovac ore deposit (Boranja Mt., Serbia) was refined using the X‐ray powder diffraction (XRPD) Rietveld method in the space group Pbam to a final RB=7.45% and RF=5.26%. It has the unit cell dimensions of: a= 9.2515(2) Å; b= 12.3109(2) Å; c= 3.03712 (7) Å; and V= 345.91(1) Å3. The calculated distances and angles are mostly in good agreement with the Mg2+‐Fe2+ substitutions across the M(1) and M(3) sites, as well as with the Fe3+‐Al3+ replacement in the M(4) site. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Furthermore, it was previously shown that various tilting and orientations of the polyhedrons and polyhedral chains in other phosphate tungsten bronzes could derive the different space groups of crystallization [5], which makes this problem very complex from the structural aspect. The similar observations were also confirmed in our studies of other materials [38,39]. Although crystal structure refinements were beyond of the scope of this paper, different calculated crystallographic axis and angles between PWB, Li-PWB, and Ca-PWB (Table II) could be sufficient proof of the various tilting of their WO 6 octahedrons and PO 4 tetrahedrons.…”
Section: Connection Between Bronzes' Properties Catalytic Action and Br Reaction Responsesupporting
confidence: 86%
“…Furthermore, it was previously shown that various tilting and orientations of the polyhedrons and polyhedral chains in other phosphate tungsten bronzes could derive the different space groups of crystallization [5], which makes this problem very complex from the structural aspect. The similar observations were also confirmed in our studies of other materials [38,39]. Although crystal structure refinements were beyond of the scope of this paper, different calculated crystallographic axis and angles between PWB, Li-PWB, and Ca-PWB (Table II) could be sufficient proof of the various tilting of their WO 6 octahedrons and PO 4 tetrahedrons.…”
Section: Connection Between Bronzes' Properties Catalytic Action and Br Reaction Responsesupporting
confidence: 86%
“…(v) The option that various structural variations within the samples could take place Although the crystal structure refinements are beyond the scope of this paper, our previous studies of diverse mineral species and solid solutions, have demonstrated that the different UCPs, polyhedral distortions, site occupancy factors, bond lengths, bond angles and valence units, could be influenced either by: (1) different inserted cations into the mineral structure; and/or by ( 2) diverse conditions of their formation, in particular, the temperature and pressure (Tančić 2017(Tančić , 2018Tančić and Kremenović, 2022;Tančić et al, 2012Tančić et al, , 2020Tančić et al, , 2023.…”
Section: (Iii) Presence Of Other Phasesmentioning
confidence: 99%
“…These mineral assemblages are accompanied by their resulting altered minerals (i.e., humite, chondrodite, serpentine, phlogopite, calcite, and brucite). Thus, endogenous borates in Mg-skarn deposits are systematically developed on the outermost part of the contact aureole formed at the contact between igneous rocks and dolomite protolith [2,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%